Visual culture: the potentialities of image in the formation of imaginary space of the contemporary world - de Azevedo, Ana Francisca (Geografares, 2014)
The article was derived from the opening conference of the III Colóquio Internacional “A Educação pelas imagens e suas geografias”, delivered by the author. Presents questions about how contemporary images comprise the organization of our experience in the world, intensifying the notion of visual culture as part of a biopolitical machine, articulated and perfected in modernity, with the notions of absolute space and time as linear foundations of a regime of visuality. Discusses the tension established between excessive encodings of images and the possibility of more than human geographies. Point discussions about the nature of images in geography from a photograph of Michael Nasch (1946), highlighting elements of problematization and potentialization.Keywords: maps; visual culture; spatial imagination; contemporary geography.